A match-derived relative pitch area facilitates the tactical representativeness of small-sided games for the official soccer match - Olthof, S. B. H.; Frencken, W. G. P.; Lemmink, K. A. P. M. (The Journal of Strength and Conditioning Research, 2019)
Small-sided games (SSGs) are a promising training format in soccer to replicate (situations of) the official match across all age groups. Typically, SSGs are played on a smaller relative pitch area (RPA; i.e., <150 m2) than the match (320 m2 RPA), which results in different tactical demands. To create a more precise replication of tactical match demands in SSGs with less than 11 players per team, a match-derived RPA (320 m2) may be considered because this affords a similar playing area per player. In addition, subgroup analysis is necessary to deal with the different number of players in match and SSGs. Therefore, this study aims to investigate tactical demands of matches and various SSGs—with a different number of players and played on 320 m2 RPA—in talented youth soccer players. Twelve elite soccer teams in 4 age categories (under-13, under-15, under-17, and under-19) played official matches and 4 vs. 4 + goalkeepers (GKs), 6 vs. 6 + GKs, and 8 vs. 8 + GKs. Positional data were collected to calculate tactical variables (interpersonal distances, length, width, and surface areas) for all players and for 2- and 4-player subgroups. Corresponding tactical variability (coefficients of variation expressed as percentages) was determined for all players. Results demonstrated that in each age category, with an increase in number of players, team distances increased and tactical variability decreased. Subgroup analyses revealed similar team distances in matches and SSGs with the exception of larger interpersonal distances in 4 vs. 4 + GKs than the match in under-13, under-15, and under-17. Match-derived RPA in SSGs facilitates the tactical representativeness for the match. Soccer coaches can use such SSGs for an optimal tactical match preparation.